Induction Callus From Cotyledons of Atropa belladonna L. and Evolution Ionic Content Using Plant Tissue Culture - Ahmed, Ekhlas Meteab; Ghanim, Nadhim Salim; Aziz, Wijdan Saadi (Nabatia, 2025)
This study dealt with the induction of callus tissue of the belladonna plant Atropa belladonna L. through the establishment of tissue cultures by growing cotyledons on Whites-(1934) medium (WM) supplied with different concentrations of BAP (0.0, 5.0, and 1.5) mg.L-1 and 2 4-D at level (0.0, 1.5, and 2.0) mg.L-1, Callus tissue implantation at different levels of Salicylic acid, tyrosine, Jasmonic acid, PEG, and NaCl separately. The results showed that the best fresh and dry weight was obtained from the induction of callus when adding BAP At level 1.5 mg.L-1 mixed with 2,4- D At level 2.0 mg.L-1 reached 3.97 g and 0.649 mg on straight. The results showed the highest percentage of nitrogen reached 0.98 µg.gm dry weight when adding Jasmonic acid at level 75 mg.L-1, and the highest percentage of phosphorus reached 0.67 µg.gm dry weight when adding PEG at level 0.5 gm, and the highest percentage of potassium reached 0.98 µg.gm dry weight when adding Salicylic acid at a concentration of 75 mg.L-1 , and the highest increase in calcium reached 637.0 µg.gm dry weight when adding Jasmonic acid at level 75 mg.L-1 .and the highest percentage of sodium reached 185.3 µg.gm dry weight when adding tyrosine at level 40 mg.L-1, and the highest increase in chlorine reached 178.2 µg.gm dry weight when adding NaCl at level 75 mg.L-1.